The function of Extract Curcuma (Curcuma xanthorrhiza Roxb) In Restoring Hemoglobin, erythrocyte and hematocrit 1 On Soccer Athlete - Ali Rosidi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
The purpose of this study is to determine the effect of giving temulawak (Curcuma Xanthorrhiza Roxb) in athletes after having running activity 5000 meters toward hemoglobin, erythrocyte and hematocri level. The research design is double blind randomized controlled trial. The subjects were 35 male football athletes from PPLP (Centre for Education and Training Student) Salatiga, Central Java. The subjects were divided into 5 group with different treatments; group I giving temulawak extract capsule containing curcumin (ETKK) 250 mg / day, group II ETKK 500 mg / day, group III ETKK750 mg / day, group IV were given multivitamin and mineral (MVM) capsules per day (beta carotene5000 UI, Vitamin E 200 UI, Vitamin C 500 mg, 15 mg zinc, selenium 50 mcg) and group V were given placebo whilethe capsule were given for 21 days. The giving of temulawak extract (Curcuma xanthorrhiza Roxb) gave no effect on theimprovement of hemoglobin levels, eritrsit and hematocrit in athletes after having 5000 meters running test.